Evaluasi Kerjasama Sister City Toraja Utara - New Zealand dalam Peningkatan Kualitas Sektor Pertanian dan Perkebunan di Toraja Utara - Lumalan, Carnia; Wicaksono, Arief (Journal of International and Local Studies, 2023)
Indonesia is a developing country that has the characteristics and potential of development resources that rely heavily on the agricultural sector. Indonesia is the third largest source of agricultural products for New Zealand. New Zealand invites North Toraja to cooperate in agriculture and plantations which is realized through the Sister City collaboration. The existence of sister city cooperation that is woven gives little space and hope for the people of North Toraja, especially in the realization of agricultural development goals in North Toraja. The research uses qualitative methods. Related to this research, the author uses primary data collection techniques, namely interviews and secondary data, namely literature, journals and related documents. The results showed that the sister city cooperation agreement did not run optimally, the contents of the agreement were not fully actualized and the stages were not complete. This was caused by factors, namely not being followed-up properly, the budget was limited, Human Resources were not/not ready and the parties who bridged the two partners did not carry out their duties properly. Keywords: Evaluation, Cooperation, Sister City, Toraja Utara-New Zealand